2010
DOI: 10.1089/dia.2009.0131
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Requirement Profiles of Patients with Type 2 Diabetes After Achieving Stabilized Glycemic Control with Short-Term Continuous Subcutaneous Insulin Infusion

Abstract: Initial TDD in type 2 diabetes patients on CSII showed a wide range of distribution with a TBo-to-TBa ratio >2.0 and was associated with parameters indicating glycemic control but not with body weight, suggesting that the currently used protocol in dose determination of insulin, including allocation of half of the TDD to TBa or weight-based determination of initial TDD, may need to be reexamined when treating type 2 diabetes with CSII therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…17 In all, the mean total daily insulin dose was 31.66 -9.85 IU (i.e., 0.48 -0.19 IU/ kg/day) for our 171 patients. As research on the Indian population shows, the daily insulin dose of 46 T2DM patients was 44.0 -23.7 U/day 18 (i.e., 0.61 IU/kg/day), when treatment was transitioned from MDI to CSII for 6 months, and the insulin dose was higher than that of our patients.…”
Section: Discussionmentioning
confidence: 77%
“…17 In all, the mean total daily insulin dose was 31.66 -9.85 IU (i.e., 0.48 -0.19 IU/ kg/day) for our 171 patients. As research on the Indian population shows, the daily insulin dose of 46 T2DM patients was 44.0 -23.7 U/day 18 (i.e., 0.61 IU/kg/day), when treatment was transitioned from MDI to CSII for 6 months, and the insulin dose was higher than that of our patients.…”
Section: Discussionmentioning
confidence: 77%
“…In our previous study, we observed that insulin deficiency given physiological needs is common in patients with T2DM receiving oral antidiabetic agents or insulin injections when they need to restrict calorie to achieve euglycemia and that they do not require calorie restriction to achieve euglycemia when insulin requirements are corrected for physiological needs by continuous subcutaneous insulin infusion therapy. 15 However, few patients with T2DM use continuous subcutaneous insulin infusion therapy, and therefore they require calorie restriction in addition to medical treatment to achieve euglycemia.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies support positively our findings on the basal dose proportion. A study by Noh et al [27] showed that the daily basal dose was 36 ± 12% of the TDD in Korean hospitalized subjects with type 2 diabetes after achieving normoglycemia with CSII. With regard to the Japanese subjects with type 1 diabetes, the daily basal dose during hospitalization was 27.7% of TDD in those treated with CSII therapy [28], and the basal insulin requirement was 37.3% of TDD in those adequately controlled (HbA1c ≤7.9%) with CSII therapy [29].…”
Section: Discussionmentioning
confidence: 99%